Patient and clinician perspectives of factors that influence the delivery of alcohol brief interventions in Australian primary care: a qualitative descriptive study. (2nd September 2021) - Sturgiss, Elizabeth; Lam, Tina; Russell, Grant; Ball, Lauren; Gunatillaka, Nilakshi; Barton, Chris; Tam, Chun Wah Michael; O'Donnell, Renee; Chacko, Elizabeth; Skouteris, Helen; Mazza, Danielle; Nielsen, Suzanne
Abstract: Background: Brief interventions (BIs) delivered in primary care can reduce harmful alcohol consumption. Yet, clinicians do not routinely offer BIs to reduce harmful alcohol use. Objective: We explored the perspectives of clinicians and patients about the use of alcohol BIs during consultations in Australian primary care. Methods: Semi-structured interviews and focus groups (face-to-face and virtual) were undertaken with 34 general practitioners, eight practice nurses and 17 patients. Field notes were made from audio-recordings and themes were identified using a descriptive qualitative approach with the field notes as the point of data analysis. Results: Participants identified barriers within the consultation, practice setting and wider healthcare system plus across the community which reduce the delivery of BIs in primary care including: Australian drinking norms; inconsistent public health messaging around alcohol harm; primary care not recognized as a place to go for help; community stigma towards alcohol use; practice team culture towards preventive health, including systems for recording alcohol histories; limitations of clinical software and current patient resources. Conclusion: Multiple layers of the healthcare system influence the use of BIs in primary care. Identified facilitators for embedding BIs in primary care included: (i) raising community and clinician awareness of the health harms of alcohol, (ii) reinforcing a primary care culture that promotes prevention and, (iii) supportive resources to facilitate discussion about alcohol use and strategies to reduce intake. Alcohol BIs in primary care could be further supported by community public health messages about alcohol use. Lay Summary: Alcohol is a major source of harm in the community and primary care (including family doctor and general practice settings) can play a role in reducing harmful alcohol use. When clinicians talk to their patients about alcohol use, research has shown they can reduce how much they drink each week. We spoke with general practitioners, nurses and patients in Australia to work out what is getting in the way of conversations about alcohol in primary care. We found that both clinicians and patients think we need to raise community awareness about the health harms of alcohol, that there are health system barriers, and there could be better resources to use in consultations. Low-income patients are particularly disadvantaged by financial costs associated with alcohol and counselling services when they seek help. To increase conversations about alcohol in primary care, it could be more helpful to target the broader community, the health system and primary care.